Amberlite IRC-718 ion chelating resin extraction of hazardous metal Cr (VI) from aqueous solutions equilibrium and theoretical modeling - Addala, Abdelhamid (Water science and technology : a journal of the International Association on Water Pollution Research, 2021)
Under varied conditions, the IRC 718 ion-exchange resin is used to extract chromium (VI) ions from aqueous solutions. On chromium (VI) removal effectiveness, the effects of adsorption dosage, contact time, beginning metal concentration, and pH were examined. The batch ion exchange process reached equilibrium after around 90 minutes of interaction. With an initial chromium (VI) concentration of 0.5 mg/dm3, the pH-dependent ion-exchange mechanism revealed maximal removal in the pH 2.0-10 range. The adsorption mechanism occurs between Cr (VI) determined as the electron acceptor, and IRC 718 determined as the electron donor. The equilibrium ion-exchange potential and ion transfer quantities for Amberlite IRC 718 were calculated using the Langmuir adsorption isotherm model. The overall ion exchange capacity of the resin was determined to be 187.72 mg of chromium (VI)/g of resin at an ideal pH of 6.0